The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bmjdrc-2019-000881
|View full text |Cite
|
Sign up to set email alerts
|

In vivo investigation of the tissue response to commercial Teflon insulin infusion sets in large swine for 14 days: the effect of angle of insertion on tissue histology and insulin spread within the subcutaneous tissue

Abstract: ObjectiveThis study investigated the effects of the inflammatory tissue response (ITR) to an insulin infusion set (IIS) on insulin bolus spread over wear time, as well as the effect of cannula insertion angle on the ITR, bolus shape, and pump tubing pressure.Research design and methodsAngled or straight IISs were inserted every other day for 14 days into the subcutaneous tissue of 11 swine and insulin was delivered continuously. Prior to euthanasia, a 70 µL bolus of insulin/X-ray contrast agent was infused whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Although several factors might induce inflammation at the infusion site, the specific mechanisms underlying CSII device failure have yet to be determined. Various hypotheses have been generated including mechanical barriers to insulin flow and direct toxicity from the infusion device's composition 12,15,16,28 . However, this study focused on the root causes of the inflammatory response, specifically the phenolic compound used in insulin formulations, as well as the specific cell types responsible for the inflammation induced by these insulin phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several factors might induce inflammation at the infusion site, the specific mechanisms underlying CSII device failure have yet to be determined. Various hypotheses have been generated including mechanical barriers to insulin flow and direct toxicity from the infusion device's composition 12,15,16,28 . However, this study focused on the root causes of the inflammatory response, specifically the phenolic compound used in insulin formulations, as well as the specific cell types responsible for the inflammation induced by these insulin phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses have been generated including mechanical barriers to insulin flow and direct toxicity from the infusion device's composition. 12,15,16,28 However, this study focused on the root causes of the inflammatory response, specifically the phenolic compound used in insulin formulations, as well as the specific cell types responsible for the inflammation induced by these insulin phenolic compounds. These studies demonstrated that commercial insulin formulations containing phenolic compounds are highly cytotoxic.…”
Section: Day 7 Insulin Infusion In Diabetic Micementioning
confidence: 99%
“…[1][2][3][4] The reasons for unexplained hyperglycemia remain unknown, although several hypotheses propose local inflammation of the subcutaneous tissue at the infusion site as a likely cause. [5][6][7][8][9][10][11] Continuous glucose monitors (CGM) are also long-dwelling, subcutaneously placed devices augmenting pump therapy, which have faced challenges in maintaining patency over time due to localized inflammation. [12][13][14] Multiple efforts to temper such inflammation through the use of locally administered anti-inflammatory agents, such as corticosteroids, have been reported with some success.…”
Section: Introductionmentioning
confidence: 99%
“…1 -4 The reasons for unexplained hyperglycemia remain unknown, although several hypotheses propose local inflammation of the subcutaneous tissue at the infusion site as a likely cause. 5 -11…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, the catheter material, shape, size, insulin aggregates/amyloids, and the infused preservative in an insulin formulation could all contribute to the FBR. Other challenges include the exposed wound, the catheter insertion device, the catheter’s needle, and perhaps the catheter insertion angle. FBR at an insulin device location cumulatively contributes to local skin irritation due to leukocyte recruitment and activation of the inflammatory cascade. Independent of the initiating source(s) of inflammatory cell recruitment, accumulation of leukocytes and associated proteases at insulin infusion sites could lead to increased insulin uptake and/or insulin degradation by inflammatory cells leading to an exacerbation of the inflammatory response and ultimately altering insulin absorption and blood glucose control.…”
mentioning
confidence: 99%